Um estudo sobre a importância do laboratório de ensino de matemática no desenvolvimento da prática docente na educação básica - Diniz, Rafael da Silva (2025)
The use of laboratories in elementary and high schools is still limited, despite being an effective approach to implementing active learning methodologies. In general, spaces dedicated to experimentation are more commonly associated with the Natural Sciences, leaving other fields, such as Mathematics, underrepresented in this context. This study aims to reflect on the potential of the Mathematics Teaching Laboratory (LEM) as a pedagogical environment that fosters scientific experimentation in Basic Education. The objective is to explore how the LEM can encourage the development of talents and skills in children and adolescents, sparking interest in scientific research and contributing to more meaningful learning. Furthermore, the study considers the importance of aligning laboratory practices with mandatory curricula, providing a comprehensive education that stimulates critical thinking and the construction of mathematical knowledge.